Guidelines of Using Project Management Tools and Techniques to Mitigate Factors Causing Delays in Public Construction Projects in Kingdom of Saudi Arabia - Alotaibi, Nasser Obaid; Sutrisna, Monty; Chong, Heap Yih (2016)
Delays can be considered a common problem within public and private construction projects around the world but the problem is endemic in Kingdom of Saudi Arabia (KSA) where massive public funds are lost every year as a result. Delays may have significant negative impact not only to the KSA public construction projects but also on its economic and social status. Although several studies have examined the factors influencing delays in public construction projects in KSA, little attention has been paid to how project management tools and methods have made any impact to the incidence of project delays. This paper aims to develop the mapping and the guidelines using the principles of Project Management, after reviewing the critical factors for delays in public construction projects in the KSA. A careful attention was given to investigate the critical factors that are causing delays in building projects within public sector in KSA and the current practices of project management applications in order to develop guidelines to effectively mitigate construction delays in KSA. This review paper reports the top critical factors associated with delays in construction projects in KSA. It also identify project management tools and techniques that if implemented properly have the potentials to address the main factors contributing to the occurrence of delays. Following this, a new guideline to utilize Project Management tools and techniques in addressing the identified delay factors is also provided here with the view to help practitioners to minimize the potentials of construction delays in the KSA public projects.